2021
DOI: 10.1016/j.ijnss.2021.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Operating room nurses’ lived experiences of ethical codes: A phenomenological study in Iran

Abstract: Objective Operating room nurses, as essential members of health care teams, often face ethical challenges in the operating room. By using the ethical experiences of operating room nurses, a better understanding of ethics in the operating room can be achieved, which can lead to better nursing decisions in the face of these challenges. Therefore, this study was conducted to investigate operating room nurses’ lived experiences of ethical codes. Methods A hermeneutic phenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…45 Aghamohammadi et al elaborated on the ethical guidelines for operating room nurses, highlighting the importance of maintaining professional conduct and protecting the patient's dignity. 46 A separate study suggested a correlation between the moral awareness of operating room nurses and ethical conduct. 47 Based on our research, participants associated ethical conduct with professionalism rather than moral behavior.…”
Section: Discussionmentioning
confidence: 99%
“…45 Aghamohammadi et al elaborated on the ethical guidelines for operating room nurses, highlighting the importance of maintaining professional conduct and protecting the patient's dignity. 46 A separate study suggested a correlation between the moral awareness of operating room nurses and ethical conduct. 47 Based on our research, participants associated ethical conduct with professionalism rather than moral behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings of the opinions of operating room nurses were also reported previously. [ 28 29 ] Peñataro-Pintado et al . (2021)[ 30 ] reported that some of the key issues that affected the perioperative nurses’ ability to achieve their duties and guarantee patient safety were the stress of working in the operating room, unsuccessful announcement in the multidisciplinary group, and time pressures.…”
Section: Discussionmentioning
confidence: 99%
“…Without ethics, they may be confused about ethical issues and may not know what is the right service to give to patients. 46 The COVID-19 pandemic presents challenges and opportunities for nurses' professional and ethical compliance. On the one hand, the nursing team is affected by increased patient numbers, clinical complexity, sudden and unpredictable staff reductions, and lack of family member or caregiver support.…”
Section: Discussionmentioning
confidence: 99%
“…Without ethics, they may be confused about ethical issues and may not know what is the right service to give to patients. 46…”
Section: Discussionmentioning
confidence: 99%